Intra-Abdominal Hypertension Is More Common Than Previously Thought: A Prospective Study in a Mixed Medical-Surgical ICU. Issue 6 (June 2018) - Murphy, Patrick B.; Parry, Neil G.; Sela, Nathalie; Leslie, Ken; Vogt, Kelly; Ball, Ian
Abstract : Objectives: To determine the prevalence of intra-abdominal hypertension in mixed medical-surgical critically ill patients using modern definitions and measurement techniques. Secondarily to determine variables associated with intra-abdominal hypertension and ICU mortality. Design: A prospective observational study. Setting: Single institution trauma, medical and surgical ICU in Canada. Patients: Consecutive adult patients admitted to the ICU ( n = 285). Intervention: Intra-abdominal pressure measurements twice a day during admission to the ICU. Measurements and Main Results: In 285 patients who met inclusion criteria, 30% were diagnosed with intra-abdominal hypertension at admission and a further 15% developed intra-abdominal hypertension during admission. The prevalence of abdominal compartment syndrome was 3%. Obesity, sepsis, mechanical ventilation, and 24-hour fluid balance (> 3 L) were all independent predictors for intra-abdominal hypertension. Intra-abdominal hypertension occurred in 28% of nonventilated patients. Admission type (medical vs surgical vs trauma) was not a significant predictor of intra-abdominal hypertension. Overall ICU mortality was 20% and was significantly higher for patients with intra-abdominal hypertension (30%) compared with patients without intra-abdominal hypertension (11%). Intra-abdominal hypertension of any grade was an independent predictor of mortality (odds ratio, 3.33; 95% CI, 1.46–7.57). Conclusions: Intra-abdominal hypertension is common in both surgical and nonsurgical patients in the intensive care setting and was found to be independently associated with mortality. Despite prior reports to the contrary, intra-abdominal hypertension develops in nonventilated patients and in patients who do not have intra-abdominal hypertension at admission. Intra-abdominal pressure monitoring is inexpensive, provides valuable clinical information, and there may be a role for its routine measurement in the ICU. Future work should evaluate the impact of early interventions for patients with intra-abdominal hypertension. Abstract : Supplemental Digital Content is available in the text.